The perceptions of married men on breastfeeding practice - Muda, Siti Mariam; Mohamad Rozi, Mohamad Syahmi; Mohamad Arifin, Siti Roshaidai; Makhtar, Aniawanis (Department of Community Health, Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2017)
Background: Breastfeeding is the common practice for women soon after birth. As early as the baby is born, the mother will start to have milk production and enhance lactation period post-delivery. Thus, the mother becomes naturally embrace with the needs of breastfeeding, even for the first time mother. However, men somehow shows lack of awareness towards breastfeeding practice and have little information regarding the support required during the practice and the impacts of the support.